MYBL2 Gene Polymorphism Is Associated With Acute Lymphoblastic Leukemia Susceptibility in Children - Guo, Haixia; Li, Na; Sun, Yaping; Wu, Cuiling; Deng, Huixia; Xu, Ling; Yang, Xu (Frontiers in Oncology, 2021)
Purpose Although MYBL2 had been validated to participate in multiple cancers including leukemia, the role of MYBL2 polymorphisms in acute lymphoblastic leukemia (ALL) was still not clear. In this study, we aimed to evaluate the association between MYBL2 single nucleotide polymorphisms (SNPs) and ALL risk in children. Methods A total of 687 pediatric ALL cases and 971 cancer-free controls from two hospitals in South China were recruited. A case-control study by genotyping three SNPs in the MYBL2 gene (rs285162 C>T, rs285207 A>C, and rs2070235 A>G) was conducted. The associations were assessed by odds ratios (ORs) with corresponding 95% confidence intervals (CIs). Subgroup and stratification analyses were conducted to explore the association of rs285207 with ALL risk in terms of age, sex, immunophenotype, risk level, and other clinical characteristics. The false-positive report probability (FPRP) analysis was performed to verify each significant finding. Functional analysis in silico was used to evaluate the probability that rs285207 might influence the regulation of MYBL2. Results Our study demonstrated that rs285207 was related to a decreased ALL risk (adjusted OR = 0.78; 95% CI = 0.63-0.97, P = 0.022) in the dominant model. The associations of rs285207 with ALL risk appeared stronger in patients with pre B ALL (adjusted OR=0.56; 95% CI=0.38-0.84, P=0.004), with normal diploid (adjusted OR=0.73; 95% CI=0.57-0.95, P=0.017), with low risk (adjusted OR=0.68; 95% CI=0.49-0.94, P=0.021), with lower WBC (adjusted OR=0.62; 95% CI=0.43-0.87, P=0.007) or lower platelet level (adjusted OR=0.76; 95% CI=0.59-0.96, P=0.023). With FPRP analysis, the significant association between the rs285207 polymorphism and decreased ALL risk was still noteworthy (FPRP=0.128). Functional analysis showed that IKZF1 bound to DNA motif overlapping rs285207 and had a higher preference for the risk allele A. As for rs285162 C>T and rs2070235 A>G, no significant was found between them and ALL risk. Conclusion In this study, we revealed that rs285207 polymorphism decreased the ALL risk in children, and rs285207 might alter the binding to IKZF1, which indicated that the MYBL2 gene polymorphism might be a potential biomarker of childhood ALL.